'STRANGE' RHETORIC AND HOMERIC RECEPTION IN AELIUS ARISTIDES' EMBASSY SPEECH TO ACHILLES (OR. 52). (October 2021) - Sansom, Stephen A.
Abstract : This article argues that Aelius Aristides adapts the word atopos ('strange', 'out of place') as figured speech in his Embassy Speech to Achilles, meaning something that is either illogical according to rhetorical topoi or inconsistent with the text of Homer's Iliad . By doing so, he not only expands the semantic range of atopos but also comments on the rhetorical, intertextual, and pedagogical relationship between oratory and the Homeric tradition.